KESELARASAN ANTARA KEBUTUHAN BAHASA INGGRIS DENGAN MATERI AJAR BAHASA INGGRIS MAHASISWA JURUSAN AKUTANSI - Ratmanida, Ratmanida (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2012)
This study is aimed at describing and explaining a match between the  need of English for academic and occupational purposes of Accounting students in Padang with it’s English  teaching materials. Data of this study were obtained from questionnaire, interview and observation. Participants of this study wer accounting students, lecturers who teach English at Accounting departement, and accountants   at several Banks in Padang.  The findings of the study revealed that the English teaching materials of Accounting Departement  was less correlated with Accounting students needs.  In addition, there was also less correlation between Accountants  English needs with English teaching materials in Accounting Departement in Padang.